2013
DOI: 10.1007/s00414-013-0858-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the genetic background of different Colombian populations using the SNPforID 52plex identification panel

Abstract: Various strategies for analysing SNP markers and genotyping have been published with the goal of obtaining informative profiles from biological samples that contain only small amounts of template and/or degraded DNA. In this study, a multiplex assay of 52 autosomal single-nucleotide polymorphisms (SNPs) was used to analyse 438 individuals from urban populations from different regions of Colombia, as well as a sample of 50 Native American individuals of the Pastos ethnic group from Nariño. To determine if signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The World Marrow Donor Association 2014 database reported that, in Colombia, 92.6% of transplanted UCB units are imported through European or North American BM donor registries. Unfortunately, the imported units do not satisfy current HLA matching demands for hematopoietic transplantation, probably due to the multiethnic migration history of the country . Despite the lack of established policy and legislation regarding a national BM donor registry, support from the District and National Governments led to the implementation of a public UCB bank in Colombia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Marrow Donor Association 2014 database reported that, in Colombia, 92.6% of transplanted UCB units are imported through European or North American BM donor registries. Unfortunately, the imported units do not satisfy current HLA matching demands for hematopoietic transplantation, probably due to the multiethnic migration history of the country . Despite the lack of established policy and legislation regarding a national BM donor registry, support from the District and National Governments led to the implementation of a public UCB bank in Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…to the multiethnic migration history of the country. 34 Despite the lack of established policy and legislation regarding a national BM donor registry, support from the District and National Governments led to the implementation of a public UCB bank in Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Amerindian ancestry did not influence self-reported ethnicity or declared family origin probably because it was the minor contributor to the genetic background of our populations, finding also described by other authors in distinct Brazilians subpopulations Moura et al 2015). Ancestry stratification of individuals or populations can be achieved by using different strategies such as INDEL or SNPs markers, and different panels have been created for this end (Ibarra et al 2014;Resque et al 2010;Silva et al 2010;Yang et al 2005). INDEL panels have the advantage of reduced cost in comparison to SNPs panels as it allows to genotype several markers in multiplex fashion by a best value.…”
Section: Discussionmentioning
confidence: 99%
“…Argentina, Costa Rica and Antioquia have a tri-hybrid population and, for autosomal markers, they show marked European ancestry, followed by Native American ancestry, and a smaller percentage of African ancestry. The African ancestry is very small in Argentina (65% E, 4% A, 31% NA [27]) and in Costa Rica (58% E, 4% A, 38% NA [28]), compared with the percentages in Antioquia (44.3% E, 21.1% A, 34.6% NA [29]). For markers of X chromosome, the population of Antioquia carries genetic heritage of 37.5% E, 29% A and 33.5% NA, showing greater European contribution, which is very close to the Native American data [30].…”
Section: Resultsmentioning
confidence: 92%